Philosophy of Politics in Jadid Thought - Turobov Yorqinjon Yoqub o‘g‘li (International Journal on Integrated Education, 2026)
This article provides a scholarly analysis of the political and philosophical views of the Jadid movement. In Jadid thought, political philosophy was formed in close connection with the ideas of enlightenment, social justice, national awakening, and legal consciousness. The article examines the Jadid intellectuals’ perspectives on state–society relations, political reforms, the development of political awareness among the people, and the protection of national interests. It argues that the political-philosophical legacy of the Jadids served as an important theoretical foundation for the development of national consciousness and political thought under colonial conditions.